Towards a Macro-Level Theoretical Understanding of Police Services’ Acquisition of Risk Technologies - Hill, Dallas; O’Connor, Christopher (Surveillance & Society, 2024)
Most North American police services have rapidly acquired and implemented a range of emerging and disruptive technologies in recent years. This rapid adoption of technologies has left a significant gap in our theoretical understanding of how police make decisions about which technologies to acquire. While existing research has focused on technology’s impact at the organizational level, the macro-level context that shapes technological acquisition by the police is undertheorized. To address this gap in the literature, this article combines theorizing by Ericson and Haggerty (1997) on policing the risk society (PRS) and Zuboff (2019) on surveillance capitalism (SC) to develop a macro-level theoretical framework. We consider technologies acquired by the police to be risk technologies and argue that combining key elements of PRS and SC theorizing offers a macro-level understanding of police decision-making about which technologies to adopt that can complement meso-level organizational theories. While calling for additional empirical research, this article concludes by discussing the potential impacts associated with private-sector involvement in public-sector initiatives and providing directions for future research.